Estimating contralateral breast exposure from breast cancer radiotherapy in clinical practice - Bese, N.; Iribas, A.; Goksel, E.; Dirican, A.; Senkesen, O.; Kucucuk, H.; Tezcanli, E.; Uras, C.; Sengoz, M. (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
European Breast Cancer Conference, Barcelona, SPAIN, MAR 24-24, 2010